(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The differential and integral inequalities form a subtopic of the mathematical inequalities and are discussed at length by several authors all over the world. The differential inequalities are the integration of the differential inequalities which may be called the general comparison principle. An integral inequality is a solution to the related integral inequality. By both, we mean a process of finding the bounds on the solution set of the related differential or integral inequalities. In this study, we have discussed abstract analysis, derivatives and differential inequalities, integration and integral inequalities, nonlinear analysis.